2001
DOI: 10.1083/jcb.200103071
|View full text |Cite
|
Sign up to set email alerts
|

Reorganization of multivesicular bodies regulates MHC class II antigen presentation by dendritic cells

Abstract: Immature dendritic cells (DCs) sample their environment for antigens and after stimulation present peptide associated with major histocompatibility complex class II (MHC II) to naive T cells. We have studied the intracellular trafficking of MHC II in cultured DCs. In immature cells, the majority of MHC II was stored intracellularly at the internal vesicles of multivesicular bodies (MVBs). In contrast, DM, an accessory molecule required for peptide loading, was located predominantly at the limiting membrane of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

20
255
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 258 publications
(275 citation statements)
references
References 64 publications
(92 reference statements)
20
255
0
Order By: Relevance
“…DC maturation-associated reorganization of lysosomes has been noted previously in a murine DC line and may account for efficient transport of MHC class II molecules from lysosomes to the plasma membrane during DC maturation (39). In human monocyte-derived DCs analyzed in the present study we also observed that lysosomes are deprived of MHC class II after maturation and loose their tightly packed membranes (Fig.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…DC maturation-associated reorganization of lysosomes has been noted previously in a murine DC line and may account for efficient transport of MHC class II molecules from lysosomes to the plasma membrane during DC maturation (39). In human monocyte-derived DCs analyzed in the present study we also observed that lysosomes are deprived of MHC class II after maturation and loose their tightly packed membranes (Fig.…”
Section: Discussionsupporting
confidence: 85%
“…Three pathways of delivery from lysosomes to the plasma membrane have been described. Tubulation and vesicle formation of the lysosome were proposed to account for delivery of MHC class II molecules to the plasma membrane during DC maturation (39). Previously, a specialized CIIV vesicle was identified in murine DC and was also proposed as a delivery route for MHC class II during DC maturation (7).…”
Section: Discussionmentioning
confidence: 99%
“…In maturing DCs, transport of MHCII is mediated via membrane tubules that radiate out from the MIIC toward the plasma membrane, and this pathway depends on an intact microtubule network (Kleijmeer et al 2001;Boes et al 2002Boes et al , 2003Chow et al 2002;Vyas et al 2007;van Nispen tot Pannerden et al 2010). MHCII, DM, and LAMP1 are not enriched in these tubules relative to the vacuolar endosomes from which they derive, suggesting that this pathway may not require active recruitment but is entered by default (Kleijmeer et al 2001).…”
Section: Trafficking Of Pmhciimentioning
confidence: 99%
“…In professional antigen-presenting cells, the organelles at which MHCII peptide loading occurs mainly constitute late endosomes, although lysosomes have also been implicated (Geuze 1998). Together, these endocytic compartments are also referred to as MHCII compartments (MIICs) (Peters et al 1991;Kleijmeer et al 1997Kleijmeer et al , 2001). DCs constitutively synthesize MHCII, which, in the absence of pathogen, are all loaded with "self " peptides in MIICs.…”
mentioning
confidence: 99%
“…In eukaryotic cells, the MVB pathway controls various important processes such as receptor down-regulation, antigen presentation, cytokinesis, retroviral budding, and autophagy (1)(2)(3)(4)(5)(6). In the budding yeast Saccharomyces cerevisiae, previous studies identified a number of genes involved in vacuolar protein sorting (VPS) (7,8).…”
mentioning
confidence: 99%